All-solid-state battery and application thereof

By providing a first electrolyte membrane with a porous structure on the negative electrode sheet side of an all-solid state battery, the problem of deterioration of interface contact caused by volume expansion of the negative electrode sheet is solved, and the cycle stability and energy efficiency of the battery are improved.

CN119627195APending Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411824934.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the charging and discharging cycle of all solid-state batteries, the volume expansion of the negative electrode sheet leads to deterioration of interface contact, affecting the cycle stability and service life of the battery.

Method used

A first electrolyte membrane with a porous structure is provided on the negative electrode sheet side of the all-solid state battery to provide a buffer space, increase the ion transmission path between the electrode and the solid electrolyte membrane, and enhance the stability of the solid electrolyte membrane.

Benefits of technology

By dispersing the stress generated by volume expansion of the negative electrode sheet, the integrity and stability of the interface are maintained, the interface impedance is reduced, and the cycle stability and energy efficiency of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627195A_ABST
    Figure CN119627195A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state battery and application thereof, the all-solid-state battery at least comprises: a first electrolyte membrane, which is arranged on the negative pole piece side of the all-solid-state battery and has a porous structure, and the ionic conductivity of the first electrolyte membrane is 1 * 10 <-4 > S / cm to 2 * 10 <-2 > S / cm; and the second electrolyte membrane is arranged on the positive pole piece side of the all-solid-state battery, and the ionic conductivity of the second electrolyte membrane is 1 * 10 <-4 > S / cm to 2 * 10 <-2 > S / cm. According to the all-solid-state battery and the application thereof provided by the invention, a buffer space can be provided for volume expansion of the negative pole piece, an ion transmission path between the electrode and the solid-state electrolyte membrane is increased, and the stability of the solid-state electrolyte membrane is enhanced, so that the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to an all-solid-state battery and applications thereof. Background Art

[0002] All-solid-state batteries have the potential for high energy density, excellent safety performance, and long cycle life, and have become an important development direction for the next generation of battery technology. However, during the charge and discharge cycle of all-solid-state batteries, the volume of the negative electrode plate will expand, which will lead to the deterioration of the interface contact between the negative electrode plate and the solid electrolyte, seriously affecting the cycle stability and service life of the battery. On the other hand, it will lead to side reactions of the solid electrolyte, aggravating the instability of the interface, which will further lead to the rapid decline of battery performance. Summary of the invention

[0003] The present invention proposes an all-solid-state battery and its application. The all-solid-state battery and its application provided by the present invention can provide a buffer space for the volume expansion of the negative electrode plate, increase the ion transmission path between the electrode and the solid electrolyte membrane, enhance the stability of the solid electrolyte membrane, and thus improve the battery's cycle performance.

[0004] In order to solve the above technical problems, the present invention provides an all-solid-state battery, comprising at least:

[0005] The first electrolyte membrane is arranged on the negative electrode plate side of the all-solid-state battery, and the first electrolyte membrane has a porous structure, and the ion conductivity of the first electrolyte membrane is 1×10 -4 S / cm~2×10 -2 S / cm; and

[0006] The second electrolyte membrane is arranged on the positive electrode plate side of the all-solid-state battery, and the ion conductivity of the second electrolyte membrane is 1×10 -4 S / cm~2×10 -2 S / cm.

[0007] In one embodiment of the present invention, the porosity of the first electrolyte membrane is 10% to 80%, and the thickness is 1 μm to 50 μm.

[0008] In one embodiment of the present invention, the thickness of the second electrolyte membrane is 5 μm to 150 μm.

[0009] In one embodiment of the present invention, the material of the first electrolyte membrane and the second electrolyte membrane includes a sulfide electrolyte.

[0010] In one embodiment of the present invention, the chemical formula of the sulfide electrolyte is Li a P 1-b M b S cO d X e , wherein, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.

[0011] In an embodiment of the present invention, M is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 < b ≤ 0.1.

[0012] In an embodiment of the present invention, the chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q z , wherein, 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.

[0013] In an embodiment of the present invention, E is Mg, Q is Cl, and the value range of g is 0.01 ≤ g ≤ 0.1.

[0014] In an embodiment of the present invention, the first electrolyte membrane is obtained by the following method:

[0015] Mix the electrolyte material and the halide evenly to obtain a mixed raw material;

[0016] Coat the mixed raw material on a substrate and perform vacuum heat treatment to dry the mixed raw material; and

[0017] Peel the dried mixed raw material and the substrate to obtain the first electrolyte membrane.

[0018] The present invention also provides an electronic device, including the all-solid-state battery described above.

[0019] In summary, the present invention proposes an all-solid-state battery and its application. By improving the solid electrolyte membrane in the all-solid-state battery and arranging a first electrolyte membrane with a porous structure on the negative electrode side, a buffer space can be provided for the volume expansion of the negative electrode, which helps to disperse the stress generated by the volume expansion of the negative electrode, maintain the integrity and stability of the interface between the negative electrode and the solid electrolyte membrane, reduce the formation and expansion of interface cracks, reduce the risk of interface impedance and solid electrolyte membrane cracking, and improve the cycle stability and energy efficiency of the battery. It can provide more interface contact points and ion transmission channels, increase the ion transmission path between the electrode and the solid electrolyte membrane, and further improve the performance of the battery. It can improve the stability of the solid electrolyte membrane to the positive and negative electrodes and to the air, and further improve the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0021] Figure 1 This is a graph showing the results of a room temperature cycle performance test on the all-solid-state battery in Example 3 of the present invention. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0024] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The present invention proposes an all-solid-state battery, for example, including a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane includes, for example, a first electrolyte membrane and a second electrolyte membrane, the first electrolyte membrane is arranged on the negative electrode sheet side, and the first electrolyte membrane has a porous structure, and the second electrolyte membrane is arranged on the positive electrode sheet side. In the all-solid-state battery provided by the present invention, the first electrolyte membrane can provide a buffer space for the volume expansion of the negative electrode sheet, maintain the integrity and stability of the interface between the negative electrode sheet and the solid electrolyte membrane, reduce the interface impedance, and improve the cycle stability and energy efficiency of the battery. Moreover, the first electrolyte membrane can provide more interface contact points and ion transmission channels, increase the ion transmission pathway between the electrode and the solid electrolyte membrane, and further improve the overall performance of the battery. In the present invention, the all-solid-state battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the types and types of the all-solid-state battery.

[0026] In one embodiment of the present invention, the positive electrode plate includes, for example, a positive electrode active layer, and the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a positive electrode conductive agent, and a positive electrode binder. Among them, the present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent, and the positive electrode binder, which can be selected according to actual needs. In other embodiments of the present invention, in addition to the positive electrode active layer, the positive electrode plate may also include a positive electrode collector, and the positive electrode collector is coated with a positive electrode active layer on the surface of at least one side. Among them, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.

[0027] In one embodiment of the present invention, in the positive electrode active layer, the positive electrode active material is selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA), the positive electrode electrolyte is a halide solid electrolyte, the positive electrode conductor is selected from at least one of graphite, graphene, conductive carbon black (SuperP), nanocarbon fiber (vapor-grown carbon fiber, VGCF) or carbon nanotubes, and the positive electrode binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylpyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAN), etc. At least one of polyol, polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, fluorine rubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.

[0028] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The positive electrode conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the positive electrode binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, the positive electrode sheet is directly obtained by dry pressing.

[0029] In another embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The positive electrode conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the positive electrode binder is, for example, PTFE. The positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent, and the positive electrode binder are mixed evenly in a mass ratio of, for example, 69:29:1:1, and then rolled and covered on the surface of the aluminum foil to obtain a positive electrode sheet.

[0030] In one embodiment of the present invention, the negative electrode plate is selected from at least one of a metal lithium plate, a metal indium plate or a lithium indium alloy plate. In another embodiment of the present invention, the negative electrode plate includes, for example, a negative electrode active layer, and the negative electrode active layer includes, for example, a negative electrode active material, a negative electrode electrolyte, a negative electrode conductive agent and a negative electrode binder. Among them, the present invention does not limit the mass ratio of the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent and the negative electrode binder, and can be selected according to actual needs. In other embodiments of the present invention, in addition to the negative electrode active layer, the negative electrode plate may also include a negative electrode current collector, and the surface of at least one side of the negative electrode current collector is coated with a negative electrode active layer. Among them, the negative electrode current collector is, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector.

[0031] In one embodiment of the present invention, in the negative electrode active layer, the negative electrode active material is selected from at least one of graphite materials or silicon materials, the negative electrode electrolyte is, for example, a sulfide electrolyte, the negative electrode conductive agent is selected from at least one of graphite, graphene, SuperP, VGCF or carbon nanotubes, and the negative electrode binder is selected from at least one of PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, polyurethane, PVA, Alg, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.

[0032] In one embodiment of the present invention, the negative electrode active material is, for example, silicon, the negative electrode electrolyte is, for example, a sulfide electrolyte, the negative electrode conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1, and the negative electrode binder is, for example, SBR. After the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent and the negative electrode binder are uniformly mixed in a mass ratio of, for example, 72:20:5:3, the negative electrode sheet is directly obtained by dry pressing.

[0033] In another embodiment of the present invention, the negative electrode current collector is, for example, a copper foil current collector, the negative electrode active material is, for example, silicon, the negative electrode electrolyte is, for example, a sulfide electrolyte, the negative electrode conductive agent includes, for example, SuperP and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1, and the negative electrode binder is, for example, SBR. After the negative electrode active material, the negative electrode electrolyte, the negative electrode conductive agent and the negative electrode binder are uniformly mixed in a mass ratio of, for example, 72:20:5:3, they are rolled and covered on the surface of the copper foil current collector to obtain a negative electrode sheet.

[0034] In one embodiment of the present invention, the thickness of the solid electrolyte membrane is, for example, 5 μm to 200 μm, and the ionic conductivity is, for example, 1×10 -4 S / cm~2×10 -2 Specifically, in the solid electrolyte membrane, the porosity of the first electrolyte membrane is, for example, 10% to 80%, the thickness is, for example, 1 μm to 50 μm, and the ionic conductivity is, for example, 1×10 -4 S / cm~2×10 -2 S / cm, the thickness of the second electrolyte membrane is, for example, 5 μm to 150 μm, and the ionic conductivity is, for example, 1×10 -4 S / cm~2×10 -2S / cm. By controlling the thickness and porosity of the first electrolyte membrane, while ensuring that the solid electrolyte membrane has appropriate ionic conductivity, the first electrolyte membrane can fully adapt to the expansion of the negative electrode sheet, and can disperse all the stress generated by the volume expansion of the negative electrode sheet, thereby improving the cycling performance of the all-solid-state battery and extending the service life of the battery. Moreover, by controlling the thickness of the second electrolyte membrane, the cycling performance of the battery can be further improved and the service life of the battery can be extended.

[0035] In one embodiment of the present invention, in the solid electrolyte membrane, the material of the first electrolyte membrane includes a sulfide electrolyte, which can improve the interfacial stability between the solid electrolyte membrane and the negative electrode sheet, ensure a continuous and stable lithium-ion transport channel, reduce the interfacial impedance, and improve the charge transfer efficiency. Specifically, the chemical formula of the sulfide electrolyte is selected from, for example, Li a P 1- b M b S c O d X e or Li f P 1-g E g S w O g Q z and at least one of the like. Among them, in Li a P 1-b M b S c O d X e 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, etc., and X is selected from at least one of Cl, Br or I, etc. Further, M is, for example, selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is, for example, 0 < b ≤ 0.1. More specifically, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of M and X elements and the value range of b in the sulfide electrolyte, the cycling performance of the battery can be improved, and thus the service life of the battery can be extended.

[0036] In one embodiment of the present invention, when the chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q zWhen 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn, Pb, etc., and Q is selected from at least one of Cl, Br, I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the type of element E, the type of element Q, and the value range of g in the sulfide electrolyte, the cycle performance of the battery can be improved, thereby extending the service life of the battery.

[0037] In an embodiment of the present invention, when preparing the first electrolyte membrane, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the sulfide electrolyte Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z , after uniformly mixing the Li source, P source, M source, S source, and X source, or the Li source, P source, E source, S source, and Q source according to stoichiometry, for example, placing them in a ball mill jar for ball milling treatment to obtain precursor powder, and then performing high-temperature annealing sintering on the precursor powder to obtain a sulfide electrolyte. Then, the sulfide electrolyte and the halide are uniformly mixed to obtain a mixed raw material, and a binder and a solvent are added and mixed uniformly to obtain an electrolyte slurry, which is then coated on a substrate. Next, the substrate coated with the electrolyte slurry is subjected to vacuum heat treatment. After drying the electrolyte slurry, the electrolyte slurry and the substrate are peeled off to obtain the first electrolyte membrane. Among them, since the halide can decompose at high temperature, when the substrate coated with the electrolyte slurry is subjected to vacuum heat treatment, the halide in the electrolyte slurry will decompose into gaseous products and volatilize, and voids will be formed at the positions of the halide in the electrolyte slurry, thereby obtaining a first electrolyte membrane with a porous structure. Moreover, the gaseous products decomposed from the halide will undergo a halogenation reaction with the surface of the sulfide electrolyte particles in the electrolyte slurry, forming a lithium halide-like compound coating on the surface of the sulfide electrolyte particles. The lithium halide-like coating can prevent the sulfide electrolyte from directly contacting the positive and negative electrode plates or air, improve the stability of the sulfide electrolyte against the positive and negative electrodes and air, and further improve the overall stability of the first electrolyte membrane and the solid electrolyte membrane, ultimately improving the performance of the battery.

[0038] In one embodiment of the invention, during the preparation of the first electrolyte membrane, the Li source is selected from at least one of Li2S, LiCl, LiBr or LiI, the P source is P2S5, the M source is an oxide of M, the S source is from at least one of a Li source or a P source, the X source is from a Li source, the E source is an oxide of E, the Q source is from a Li source, the ball material mass ratio is (1-100):1, the ball milling time is 1h-48h, and the rotation speed is 50rpm. The sintering speed is, for example, 400°C to 600°C, the sintering time is, for example, 1h to 48h, the mass ratio of the halide and sulfide electrolytes is, for example, 1:(1 to 100), the halide is selected from at least one of lithium hexafluorophosphate, ammonium hydrogen fluoride, ammonium fluoride, ammonium chloride, ammonium bromide or ammonium iodide, and the binder is, for example, selected from PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, polyurethane, PVA, Alg, ethylene-propylene-diene monomer, styrene-butadiene rubber At least one of rubber, polyvinylidene fluoride, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer, etc., the solvent is, for example, selected from toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, At least one of ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, the content of the mixed raw material in the electrolyte slurry is, for example, 30wt% to 90wt%, the content of the binder in the electrolyte slurry is, for example, 0.1wt% to 10wt%, the content of the solvent in the electrolyte slurry is, for example, 10wt% to 50wt%, the method of coating the electrolyte slurry on the substrate is, for example, wet coating or electrostatic spraying, the substrate is, for example, selected from polyethylene glycol terephthalate (PET) film, smooth aluminum foil or release paper, the temperature of the vacuum heat treatment is, for example, 30°C to 250°C, and the time of the vacuum heat treatment is, for example, 1h to 24h.

[0039] In one embodiment of the present invention, in the solid electrolyte membrane, the material of the second electrolyte membrane includes a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is the same as the chemical formula of the sulfide electrolyte in the first electrolyte membrane, which will not be elaborated herein.

[0040] In one embodiment of the present invention, when preparing the second electrolyte membrane, firstly, a sulfide electrolyte is prepared according to the chemical formula of the sulfide electrolyte. The preparation process of the sulfide electrolyte is the same as the preparation process of the sulfide electrolyte in the first electrolyte membrane, and no further explanation is given here. After obtaining the sulfide electrolyte, the sulfide electrolyte, the binder and the solvent are mixed evenly to obtain an electrolyte slurry, and the electrolyte slurry is coated on the substrate. Then, the substrate coated with the electrolyte slurry is subjected to vacuum heat treatment. After drying the electrolyte slurry, the electrolyte slurry and the substrate are peeled off to obtain the second electrolyte membrane. Among them, the content of the sulfide electrolyte in the electrolyte slurry is, for example, 30wt% to 90wt%, the content of the binder in the electrolyte slurry is, for example, 0.1wt% to 10wt%, and the content of the solvent in the electrolyte slurry is, for example, 10wt% to 50wt%. The type of the binder, the type of the solvent, the type of the substrate, the method of coating the electrolyte slurry on the substrate, the temperature of the vacuum heat treatment and the time of the vacuum heat treatment are the same as the preparation process of the first electrolyte membrane, and no further explanation is given here.

[0041] In one embodiment of the present invention, after obtaining the first electrolyte membrane and the second electrolyte membrane, the first electrolyte membrane and the second electrolyte membrane are combined into a solid electrolyte membrane by rolling and isostatic pressing.

[0042] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and negative electrode sheet are placed in sequence and then sealed, for example, isostatically pressed at 500 MPa for 5 minutes to obtain an all-solid-state lithium-ion battery. The assembly process of the all-solid-state lithium-ion battery is completed in a glove box with an inert atmosphere.

[0043] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0044] Example 1

[0045] Preparation of sulfide electrolyte: Under argon atmosphere, 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 were added to a ball mill for high-energy ball milling to obtain precursor powder, wherein the ball-to-material ratio was 30:1, the rotation speed was 500 rpm, and the ball milling time was 20 h. After the ball milling, the precursor powder was sintered at 500 ° C for 10 h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide electrolytes.

[0046] Preparation of the first electrolyte membrane: Li5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 After the sulfide electrolyte and the halide ammonium bifluoride are mixed, a mixed raw material is obtained, and the mixed raw material, SBR binder and butyl butyrate solvent are mixed evenly in a mass ratio of 49:1:50 to obtain an electrolyte slurry. The electrolyte slurry is scraped onto a smooth aluminum foil using a film applicator, and after vacuum heat treatment and drying at 250°C for 5 hours, the electrolyte slurry and the smooth aluminum foil are peeled off to obtain a 1μm thick first electrolyte membrane. Among them, Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The mass ratio of the sulfide electrolyte to the halide ammonium bifluoride is 100:60.

[0047] Preparation of the second electrolyte membrane: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The sulfide electrolyte, SBR binder and butyl butyrate solvent were mixed uniformly in a mass ratio of 49:1:50 to obtain an electrolyte slurry. The electrolyte slurry was scraped onto a smooth aluminum foil using a film applicator, and after vacuum heat treatment and drying at 250°C for 5 hours, the electrolyte slurry and the smooth aluminum foil were peeled off to obtain a first electrolyte membrane with a thickness of 25 μm.

[0048] Preparation of solid electrolyte membrane: The first electrolyte membrane and the second electrolyte membrane are compounded into a solid electrolyte membrane by isostatic pressing.

[0049] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The positive electrode electrolyte, the conductive agent and the PTFE binder are mixed evenly in a mass ratio of 69:29:1:1, for example, and then the positive electrode sheet is obtained by dry pressing. The conductive agent includes SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1.

[0050] Choice of negative electrode: Li 5.5 P 0.96 Sb 0.04 S 4.40 O0.10 Cl 1.5 After the sulfide electrolyte, silicon, conductive agent and SBR binder are uniformly mixed in a mass ratio of 20:72:5:3, the negative electrode sheet is obtained by dry pressing. The conductive agent includes Super P and VGCF, and the mass ratio of Super P to VGCF is, for example, 1:1.

[0051] Battery preparation: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked, packaged, hot pressed and cold pressed in sequence to assemble into an all-solid-state battery.

[0052] Example 2

[0053] The difference between this embodiment and the first embodiment is that the thickness of the first electrolyte membrane is 5 μm by adjusting the gap of the coating blade.

[0054] Example 3

[0055] The difference between this embodiment and the first embodiment is that the thickness of the first electrolyte membrane is 10 μm by adjusting the gap of the coating blade.

[0056] Example 4

[0057] The difference between this embodiment and the first embodiment is that the thickness of the first electrolyte membrane is 50 μm by adjusting the gap of the coating blade.

[0058] Example 5

[0059] The difference between this embodiment and embodiment 2 is that the thickness of the second electrolyte membrane is 5 μm by adjusting the gap of the coating blade.

[0060] Example 6

[0061] The difference between this embodiment and embodiment 2 is that the thickness of the second electrolyte membrane is 50 μm by adjusting the gap of the coating blade.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 2 is that the thickness of the second electrolyte membrane is 150 μm by adjusting the gap of the coating blade.

[0064] Example 8

[0065] The difference between this embodiment and embodiment 2 is that: 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The mass ratio of sulfide electrolyte to ammonium bifluoride is 100:10.

[0066] Example 9

[0067] The difference between this embodiment and embodiment 2 is that: 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The mass ratio of sulfide electrolyte to ammonium bifluoride is 100:30.

[0068] Example 10

[0069] The difference between this embodiment and embodiment 2 is that: 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The mass ratio of sulfide electrolyte to ammonium bifluoride is 100:80.

[0070] Embodiment 11

[0071] The difference between this embodiment and embodiment 2 is that the halide is ammonium chloride.

[0072] Example 12

[0073] The difference between this embodiment and embodiment 2 is that the halide is ammonium bromide.

[0074] Example 13

[0075] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.99 Sb 0.0 1S 4.475 O 0.025 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.05 mol of Sb2O5.

[0076] Embodiment 14

[0077] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5.

[0078] Embodiment 15

[0079] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5.

[0080] Example 16

[0081] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.96 Sb 0.0 4S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.

[0082] Embodiment 17

[0083] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 In 0.0 1S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of In2O3.

[0084] Embodiment 18

[0085] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2S 4.47 O 0.03 Cl 1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of In2O3.

[0086] Embodiment 19

[0087] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 In 0.0 6S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of In2O3.

[0088] Embodiment 20

[0089] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of In2O3.

[0090] Embodiment 21

[0091] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.49 mol of P2S5 and 0.01 mol of In2O3.

[0092] Embodiment 22

[0093] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 Bi 0.0 1S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Bi2O3.

[0094] Embodiment 23

[0095] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li5.54 P 0.98 Bi 0.0 2S 4.47 O 0.03 Cl 1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.

[0096] Embodiment 24

[0097] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 Bi 0.0 6S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Bi2O3.

[0098] Embodiment 25

[0099] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Bi2O3.

[0100] Embodiment 26

[0101] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.

[0102] Embodiment 27

[0103] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.53 P 0.99 Mg0.0 1S 4.49 O 0.01 Cl 1.5 The raw materials are 2.015 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.01 mol of MgO.

[0104] Embodiment 28

[0105] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2S 4.48 O 0.02 Cl 1.5 The raw materials are 2.03 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO.

[0106] Embodiment 29

[0107] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.68 P 0.94 Mg 0.0 6S 4.44 O 0.06 Cl 1.5 The raw materials are 2.09 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.06 mol of MgO.

[0108] Embodiment 30

[0109] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 The raw materials are 2.15 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.1 mol of MgO.

[0110] Embodiment 31

[0111] The difference between this embodiment and embodiment 2 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2S 4.48 O 0.02 Cl 1.3 Br 0.1 I 0.1The raw materials are 2.03 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of lithium iodide, 0.49 mol of P2S5 and 0.02 mol of MgO.

[0112] Embodiment 32

[0113] The difference between this embodiment and embodiment 2 is that during the preparation of the first electrolyte membrane and the second electrolyte membrane, the binder is PVDF.

[0114] Embodiment 33

[0115] The difference between this embodiment and embodiment 2 is that during the preparation of the first electrolyte membrane and the second electrolyte membrane, the binder is PAA.

[0116] Comparative Example 1

[0117] The difference between this comparative example and Example 2 is that the chemical formula of the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl and 0.5 mol of P2S5.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 2 is that the solid electrolyte membrane only includes the second electrolyte membrane, and the thickness of the second electrolyte membrane is 30 μm.

[0120] Comparative Example 3

[0121] The difference between this comparative example and Example 2 is that: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The mass ratio of sulfide electrolyte to ammonium bifluoride is 10:100.

[0122] The compositions and parameters of the solid electrolyte membranes of various embodiments and comparative examples are shown in Table 1.

[0123] Table 1. Parameters of solid electrolyte membranes in Examples 1 to 33 and Comparative Examples 1 to 3

[0124]

[0125]

[0126] In the present invention, performance tests were performed on all-solid-state batteries prepared using different solid electrolyte membranes in Examples 1 to 33 and Comparative Examples 1 to 3.

[0127] See also Figure 1 As shown, in one embodiment of the present invention, for example, the all-solid-state battery in Example 3 is subjected to a room temperature cycle performance test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V to obtain the capacity (CC) and coulombic efficiency (CE) at different cycle numbers. Figure 1 It can be seen that with the increase in the number of cycles, the attenuation trend of the battery CC is relatively gentle, and the battery CE does not fluctuate and stabilizes at around 100%, which indicates that the battery has good cycle performance.

[0128] Please refer to Table 2. In one embodiment of the present invention, for example, the all-solid-state batteries in Examples 1 to 33 and Comparative Examples 1 to 3 are subjected to a room temperature cycle stability test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of room temperature cycles of the battery is recorded. The recorded results are shown in Table 2.

[0129] Table 2. Test results of all-solid-state batteries in Examples 1 to 33 and Comparative Examples 1 to 3

[0130] Group Normal temperature cycle number (80% SOH) Example 1 487 Example 2 968 Example 3 714 Example 4 643 Example 5 493 Example 6 832 Example 7 729 Example 8 587 Example 9 678 Example 10 533 Embodiment 11 899 Example 12 867 Embodiment 13 605 Embodiment 14 859 Embodiment 15 734 Example 16 820 Embodiment 17 599 Embodiment 18 877 Embodiment 19 781 Embodiment 20 729 Embodiment 21 777 Embodiment 22 585 Embodiment 23 859 Embodiment 24 763 Embodiment 25 711 Embodiment 26 759 Embodiment 27 589 Embodiment 28 843 Embodiment 29 747 Embodiment 30 660 Embodiment 31 743 Embodiment 32 913 Embodiment 33 918 Comparative Example 1 136 Comparative Example 2 386 Comparative Example 3 243

[0131] Please refer to Table 1 and Table 2. Comparing Examples 1-4, it can be seen that as the thickness of the first electrolyte membrane increases, the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the normal temperature cycle stability of the battery shows a trend of first increasing and then decreasing, which shows that: when the first electrolyte membrane is too thin, the first electrolyte membrane cannot fully adapt to the volume expansion of the negative electrode sheet, and cannot disperse all the stresses generated by the volume expansion of the negative electrode sheet, resulting in low normal temperature cycle stability of the battery. When the first electrolyte membrane is too thick, the surface area occupied by the pores in the first electrolyte membrane is too large, which will affect the ion conductivity of the solid electrolyte membrane, and also result in low normal temperature cycle stability of the battery. Therefore, by controlling the thickness of the first electrolyte membrane, it is possible to ensure that the solid electrolyte membrane has suitable ion conductivity while making the first electrolyte membrane fully adapt to the expansion of the negative electrode sheet, and disperse all the stresses generated by the volume expansion of the negative electrode sheet, thereby improving the cycle performance of the battery.

[0132] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 5 to 7 that, as the thickness of the second electrolyte membrane increases, the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the normal temperature cycle stability of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the thickness of the second electrolyte membrane, the cycle performance of the battery can be improved.

[0133] Please refer to Table 1 and Table 2. By comparing Example 2, Examples 8 to 10 and Comparative Examples 2 to 3, it can be seen that in sulfide electrolytes and halides, as the halide content increases, the porosity of the first electrolyte membrane gradually increases, and the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the normal temperature cycle stability of the battery shows a trend of first increasing and then decreasing, which indicates that: when the porosity of the first electrolyte membrane is too small, the first electrolyte membrane cannot fully adapt to the volume expansion of the negative electrode sheet, and cannot disperse all the stress generated by the volume expansion of the negative electrode sheet, resulting in low normal temperature cycle stability of the battery. When the porosity of the first electrolyte membrane is too large, there are too many pores in the first electrolyte membrane, which will affect the ion conductivity of the solid electrolyte membrane, and also result in low normal temperature cycle stability of the battery. Therefore, by controlling the porosity of the first electrolyte membrane, the first electrolyte membrane can be fully adapted to the expansion of the negative electrode sheet while ensuring that the solid electrolyte membrane has suitable ion conductivity, and can disperse all the stress generated by the volume expansion of the negative electrode sheet, thereby improving the cycle performance of the battery.

[0134] Please refer to Table 1 and Table 2. By comparing Examples 2, 11 and 12, it can be seen that among the three halides of ammonium bifluoride, ammonium chloride and ammonium bromide, the battery prepared with ammonium bifluoride as the halide has the largest number of cycles at room temperature, that is, the battery has the best cycle performance, which shows that: relative to HCl and HBr produced by thermal decomposition of ammonium chloride and ammonium bromide, HF and NH3 produced by thermal decomposition of ammonium bifluoride will react with the sulfide electrolyte to generate more stable LiF and Li3N, increasing the stability of the sulfide electrolyte, thereby increasing the stability of the first electrolyte membrane and the solid electrolyte membrane, and ultimately improving the battery cycle performance. Therefore, by changing the type of halide, the stability of the solid electrolyte membrane and the battery cycle performance can be changed.

[0135] Please refer to Table 1 and Table 2. Comparison of Examples 2, 13 to 15 shows that with the increase in the doping amount of the Sb element in the sulfide electrolyte, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. Comparison of Examples 17 to 20 shows that with the increase in the doping amount of the In element in the sulfide electrolyte, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. Comparison of Examples 22 to 25 shows that with the increase in the doping amount of the Bi element in the sulfide electrolyte, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the M element in the sulfide electrolyte, the cycle performance of the battery can be improved.

[0136] As shown in Table 1 and Table 2, it can be seen from the comparison of Examples 27 to 30 that, as the doping amount of the Mg element in the sulfide electrolyte increases, the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the E element in the sulfide electrolyte, the cycle performance of the battery can be improved.

[0137] As shown in Table 1 and Table 2, by comparing Example 2 with Example 16, Example 18 with Example 21, Example 23 with Example 26, and Example 28 with Example 31, it can be seen that when the doping amount of Sb, In, Bi or Mg in the sulfide electrolyte is the same, if Br and I are doped into the sulfide electrolyte, the number of normal temperature cycles of the battery will also decrease, that is, the cycle performance of the battery will decrease. Therefore, by controlling the number of element types contained in X or Q in the sulfide electrolyte, the cycle performance of the battery can be further improved.

[0138] As shown in Table 1 and Table 2, by comparing Example 2, Example 15, Example 20, Example 25 and Comparative Example 1, when the sulfide electrolyte is not doped with Sb, Bi, In or Mg elements, the number of normal temperature cycles of the battery is only 136, indicating that the Sb, Bi, In or Mg elements doped in the sulfide electrolyte can significantly improve the cycle performance of the battery. Therefore, by controlling the type of M or E elements in the sulfide electrolyte, the cycle performance of the battery can be improved.

[0139] As shown in Table 1 and Table 2, by comparing Example 2 with Examples 32-33, it can be seen that when SBR is used as a binder in the preparation process of the solid electrolyte membrane, the number of cycles of the battery at room temperature is the largest, that is, the cycle performance of the battery is the best, which shows that the type of binder affects the performance of the solid electrolyte membrane, and then affects the cycle performance of the battery. Therefore, by changing the binder in the preparation process of the solid electrolyte membrane, the cycle performance of the battery can be changed.

[0140] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.

[0141] In summary, the present invention proposes an all-solid-state battery and its application. By arranging a first electrolyte membrane with a porous structure on the side of the negative electrode plate, a buffer space can be provided for the volume expansion of the negative electrode plate, which helps to disperse the stress generated by the volume expansion of the negative electrode plate, maintain the integrity and stability of the interface between the negative electrode plate and the solid electrolyte membrane, reduce the formation and expansion of interface cracks, reduce interface impedance, and improve the cycle stability and energy efficiency of the battery. Moreover, the first electrolyte membrane with a porous structure can provide more interface contact points and ion transmission channels, increase the ion transmission path between the electrode and the solid electrolyte membrane, and further improve the performance of the battery.

[0142] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0143] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. An all-solid-state battery, characterized in that: At least: The first electrolyte membrane is arranged on the negative electrode plate side of the all-solid-state battery, and the first electrolyte membrane has a porous structure, and the ion conductivity of the first electrolyte membrane is 1×10 -4 S / cm~2×10 -2 S / cm; and The second electrolyte membrane is arranged on the positive electrode plate side of the all-solid-state battery, and the ion conductivity of the second electrolyte membrane is 1×10 -4 S / cm~2×10 -2 S / cm.

2. The all-solid-state battery according to claim 1, characterized in that: The first electrolyte membrane has a porosity of 10% to 80% and a thickness of 1 μm to 50 μm.

3. The all-solid-state battery according to claim 1, characterized in that: The second electrolyte membrane has a thickness of 5 μm to 150 μm.

4. The all-solid-state battery according to claim 1, characterized in that: The material of the first electrolyte membrane and the second electrolyte membrane includes a sulfide electrolyte.

5. The all-solid-state battery according to claim 4, characterized in that: The chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.

6. The all-solid-state battery according to claim 5, characterized in that: M is selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is 0 <b≤0.1。 7. The all-solid-state battery according to claim 4, characterized in that: The chemical formula of the sulfide electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.

8. The all-solid-state battery according to claim 7, characterized in that: E is Mg, Q is Cl, and the value range of g is 0.01≤g≤0.

1.

9. The all-solid-state battery according to claim 1, characterized in that: The first electrolyte membrane is obtained by the following method: The electrolyte material and the halide are uniformly mixed to obtain a mixed raw material; coating the mixed raw material on a substrate, and performing vacuum heat treatment to dry the mixed raw material; and The dried mixed raw material and the substrate are peeled off to obtain the first electrolyte membrane.

10. An electronic device, characterized in that: An all-solid-state battery comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Solid electrolyte structure, secondary cell and preparation method thereof

    CN108666613A

  • Composite electrolyte film for all-solid-state lithium metal negative electrode battery, preparation method of composite electrolyte film and all-solid-state sulfide lithium ion battery comprising composite electrolyte film

    CN112599846A

  • All-solid-state battery cell, preparation method thereof and all-solid-state battery

    CN114447406A

  • Preparation method of composite solid electrolyte

    CN114784372A

  • All-solid-state battery and method for manufacturing same

    CN115249808A